2005
DOI: 10.4049/jimmunol.175.8.4897
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of 4-1BB Inhibits the Development of Experimental Allergic Conjunctivitis in Mice

Abstract: The 4-1BB receptor acts as a costimulator in CD8+ T cell activation. Agonistic stimulation through this molecule by treatment with anti-4-1BB Abs has been demonstrated to inhibit various experimentally induced diseases in animals. However, the effect of anti-4-1BB Abs on experimental allergic diseases has not been reported. We investigated the effect of anti-4-1BB Abs on the development and progression of experimental allergic conjunctivitis in mice. To examine the effects of Abs during the induction or effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 36 publications
3
50
0
Order By: Relevance
“…Therefore, CD137-mediated inhibition of Th2 responses is IFN-␥ independent. This is further supported by the studies of Fukushima et al (49), which have shown that CD137 engagement by a different agonistic Ab can also inhibit both priming and effector phases of Th2-mediated experimental allergic conjunctivitis in vivo in the absence of IFN-␥. Previous studies by Zheng et al (15) have shown that CD137 costimulation induces proliferation of CD4 ϩ CD25 ϩ Treg both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, CD137-mediated inhibition of Th2 responses is IFN-␥ independent. This is further supported by the studies of Fukushima et al (49), which have shown that CD137 engagement by a different agonistic Ab can also inhibit both priming and effector phases of Th2-mediated experimental allergic conjunctivitis in vivo in the absence of IFN-␥. Previous studies by Zheng et al (15) have shown that CD137 costimulation induces proliferation of CD4 ϩ CD25 ϩ Treg both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 67%
“…The role of CD4ϩ T cells play in the development of AC has been investigated in numerous experimental settings and accumulating evidence confirms that Th2-type CD4ϩ T cells play a crucial role in the development of severe AC (9,24,28). However, the role of CD8ϩ T cells in experimental AC has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…EC is mediated by both Ag-specific IgE and Ag-specific T cells (9,12). Therefore, it could be possible that the lower eosinophil infiltration into the conjunctiva in CD8KO mice is related to altered immune responses.…”
Section: Comparison Of the Immune Responses Of Actively Immunized Wt mentioning
confidence: 99%
“…Costimulation through the 4-1BBL-4-1BB pathway provides cell proliferation and survival signals to T cells (6 -8) and can augment protection in tumor challenge models (9 -12). In contrast, 4-1BB stimulation can result in the triggering of suppressive T cell responses in certain models by diverse mechanisms (13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Ostimulatory Signals Provide Secondary Signals To T Cells mentioning
confidence: 99%